Responsibilities and Profesionalism of Judge - Dedy Sumanto (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2010)
Judicial power is the power of an independent state to hold court to conduct of lawenforcement and justice based on the Pancasila to found the law-based-state, Republic of Indonesia. This statement becomes the definition of judicial power which listed in the Article 1 of Constitutional No.4 2004. As a consequence of power sharing system that is applied in Indonesia, the judiciary or judicial functions held by judicial institutions set by the 1945 Constitution. Chapter IX of the 1945 Constitution mentions three state agencies within the scope of judicial power, i.e. the Supreme Court (MA), the Constitutional Court (MK), and the Judicial Commission (KY). However, according to the Article 24 paragraph 2, only the Supreme Court (and judicial bodies underneath it) and the Constitutional Court (MK) holds the authority as organizer of judicial power. Meanwhile, the rest of judiciaries are often referred as extra-judicial institutions.